THE FACTORS THAT AFFECTING FINANCIAL PERFORMANCE IN BANK - Putri Ayu Arista Dewi; Yusuf .; Arbia Ali; Chamariyah . (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2015)
The important of strong and healthy banking sector is really needed for economical development continuance in Indonesia which of course begins from districts to central. This condition encourages the parties involved in it to do appraisal on bank financial performance. This research is done to 10 Bank Perkreditan Rakyat in Southeast Sulawesi with the aims for knowing and analyzing the effect of CAR, LDR, BOPO and PPAP on Bank Perkreditan Rakyat financial performace (ROA) in Southeast Sulawesi. This research result shows that the improvement of CAR and BOPO will push the reduction of ROA, meanwhile LDR is not proven able to increase ROA even tended to become the cause of enhancement of ROA. Meanwhile increase of PPAP is proven to boost of ROA.